Uso de las bacterias endófitas para el mejoramiento productivo en cultivos de ciclo corto en el Cantón Babahoyo - Sánchez León, Andy Ariel (2021)
Short-cycle crops represent a very important link for the economy of our country (Ecuador), especially for the Babahoyo canton, because they generate sources of employment. Endophytic bacteria are those that, at some stage of their life, colonize the internal tissues of plants, or sometimes in large numbers, without causing damage to the hosts. These bacteria fulfill a great variety of functions such as being plant growth promoters, biological control over a diversity of phytopathogens, and improving the efficiency of the phytoremediation processes of toxic compounds in the rhizosphere. These microorganisms are inexhaustible sources of more than 20,000 biologically active compounds, which directly influence the performance and survival of host plants. Endophytic bacteria are reported to produce a number of metabolites such as antibiotics, secondary metabolites including some antitumor compounds, anti-inflammatory agents, allowing to improve agricultural productivity. There are different techniques on the use of endophytic bacteria that can be used for agricultural improvement in short-cycle crops.